The research contribution of the Schistosomiasis Collection at the Natural History Museum (SCAN): highlights, challenges and future directions - Aidan M. Emery; Muriel Rabone; Toby Landeryou; Fiona Allan; David Rollinson (Infectious Diseases of Poverty)
Abstract Background The Schistosomiasis Collection at the Natural History Museum (SCAN) is a repository of schistosomiasis-related specimens, the development of which was funded by the Wellcome Trust between 2011 and 2021. With a view to facilitating research by improving access to genetically diverse material, SCAN was built from legacy research collections of schistosomiasis-related specimens amassed over decades, with more recent collections made through partnership with large field-based projects. Methods We identified the literature associated with SCAN from 2012 until 2024, using both database searches (search terms: SCAN, the schistosomiasis collection at the NHM and schistosomiasis) and citations of the publication which originally laid out the scope of the SCAN Collection. Studies were included if the SCAN publication was cited, and/or if the SCAN Collection was utilised in the work. Data extracted included year of publication, authors, whether and how SCAN was used in the work, and type of specimens used. Results The literature includes 88 published works, demonstrating the utility of large field-based collections in supporting research. The collection comprises around half a million larval schistosomes originating from the field, with approximately 3000 specimen lots of lab-passaged adult parasites stored in liquid nitrogen. The Collection includes 11 schistosome species, the majority being the human pathogens Schistosoma haematobium and S. mansoni, while also including many livestock-associated species. Genome analysis of S. haematobium and S. guineensis samples indicate historical introgression or ongoing hybridisation. In order of representation, the collection includes S. haematobium (> 19,000 larval forms and eggs, and 550 specimen lots of laboratory passaged adult worms), S. mansoni, S. japonicum, S. bovis, S. curassoni, S. mattheei, S. rodhaini and S. guineensis, with S. intercalatum, S. margrebowiei and S. spindale represented only by laboratory-passaged isolates in liquid nitrogen. SCAN also includes around 210,000 snails, with the collection as a whole encompassing 27 countries. Conclusions Improvements in DNA sequencing techniques have allowed genome-level data to be accessed from archived larval schistosomes and allowed retrospective analysis of samples collected decades ago. SCAN has been of use in exploring schistosome diversity, particularly with reference to hybridisation and drug resistance. Multiple author nationalities demonstrate the collaborative nature of research using the Collection, although more may need to be done in future, both to promote work led by developing countries and to ensure effective collaboration and sample sharing. Graphical Abstract